A rare case of intraductal tubulopapillary neoplasm of the pancreas – case report (with video). Issue 3 (2nd April 2020) - Dalal, Ankit; Patil, Gaurav; Vadgaonkar, Amol; Maydeo, Amit
ABSTRACT: Intraductal tubulopapillary neoplasm (ITPN) is a premalignant epithelial tumor of the pancreas. We report a case of ITPN detected incidentally during histopathology examination (HPE) from a specimen taken at the time of endosonography in a patient with pancreatitis. A 53-year-old man presented with severe recurrent epigastric pain, associated with episodic nonbilious vomiting, with a weight loss of about 7 Kg since 15 days. He underwent Magnetic resonance cholangiopancreatography which showed an ovoid soft tissue lesion in the Pancreatic duct (PD) reported as possible intraductal neoplasm. Patient underwent Endoscopic Ultrasound, whereby the PD was dilated and a large hypoechoic lesion was noted in the PD (head region) causing upstream dilatation. Lesion did not show any vascularity on Doppler. Fine needle biopsy was sent from the intraductal lesion for histopathology examination (HPE). Patient then underwent an ERCP. After performing a pancreatic sphincterotomy, pancreaticoscopy was done using SPYGLASS DS system which showed a nodular intraluminal lesion in the head region with irregular and abnormal vascularity and papillary fronds. Biopsies were taken from this lesion using SpyBite biopsy forceps. To our surprise this HPE report came out to be ITPN. Patient was then referred for surgery. There is often a difference of opinion in distinguishing and classifying such tumors when compared to the subtypes of mucinous neoplasm. Identification of this neoplasm is often challenging for pathologists as well as radiologists. We present this case since it is infrequent and atypical in routine medical practice.